MCQs in neurology and neurosurgery for medical students - Natalwala, Ibrahim; Natalwala, Ammar (Master pass, 2014)
This color MCQ revision aid covers the most important basic elements from neuroanatomy, neurophysiology and neuradiology through the strokes, central nervous system lesions and malignancies